(untitled) (Canadian Journal of Native Studies, 2026)
Indigenous women were traditionally recognized as “water carriers” who played a leadership role equal to men in their communities. Since the Indian Act (1876), however, they have faced “double discrimination,” as both Indigenous and women. This paper examines Attawapiskat First Nation’s water crisis to highlight colonialism and government’s failure to coordinate a response at all levels resulting in much suffering, especially among Indigenous women and children. Drawing on the recent international WASH initiative and Anishinabek decolonizing efforts, the paper underscores the significance of a decolonial approach to water management based on the empowerment of Indigenous women and a coordinated government response to the protection of source water resources.